A practical ANP-QFD methodology for dealing with requirements' inner dependency in PSS development. (January 2019) - Fargnoli, Mario; Haber, Nicolas
Highlights: A novel methodology for the prioritization of PSS requirements is introduced. The ANP-QFDforPSS approach can augment the knowledge on QFD in PSS research. The methodology allows a holistic perception of the customers' demand. The analysis of the PSS elements' relationships depicts their mutual interactions. The methodology can be easily implemented in a software to augment its usability. Abstract: In recent years, numerous researchers have investigated the implementation of Product-Service System (PSS) in the industry as a means of enhancing companies' performances, representing a win-win solution for both companies and customers. Nevertheless, the elicitation of the customer needs and expectations through the assessment of the mutual interactions between the product's and the service's elements has been scarcely addressed. To accomplish this, the paper proposes a methodology based on the analysis of the market demand and customer requirements by means of the Quality Function Deployment for Product Service System (QFDforPSS) and the Analytic Network Process (ANP) methods. To verify the proposed methodology, it was applied to a case study in the medical devices sector, in collaboration with a provider of medical imaging equipment. Practical results showed that the proposed methodology allowed engineers to make the assessment of the PSS requirements comparable and homogenous, providing an accurate evaluation of their mutual interactions, as well as of those factors that are hidden to the customers and have an indirect effect on its satisfaction. Although the proposed approach needs to be validated through further studies in different contexts, it can be valuable for theory development and also for practitioners in the PSS field.